2003
DOI: 10.1097/01.ju.0000045707.96565.cd
|View full text |Cite
|
Sign up to set email alerts
|

Use of Medications for Erectile Dysfunction in the United States, 1996 Through 2001

Abstract: Due to the marketing of sildenafil in 1998 through 2001 the use of 2 approved medications for erectile dysfunction, namely alprostadil injection and alprostadil urethral suppository, decreased, while the use of sildenafil increased. Sildenafil was prescribed proportionately more frequently for younger men than alprostadil injection or suppository. Alprostadil was prescribed proportionately more frequently by urologists than sildenafil, which was most commonly prescribed by family and general practitioners, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 12 publications
2
16
0
1
Order By: Relevance
“…Similar condition was observed in the USA where the number of prescriptions for alprostadil injection decreased by 33% from 1998 through 2001 4 and in the UK where the cost for managing ED in NHS the ICI occupied 26.6% in 1997 and became negligible in 2000. 5 A study in Italy demonstrated that men with ED who were switched from stable ICI therapy to sildenafil expressed greater overall treatment satisfaction, better ease of use, naturalness of Three treatment modalities for erectile dysfunction B-P Jiann et al erectile process, and intention to continue treatment with sildenafil.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Similar condition was observed in the USA where the number of prescriptions for alprostadil injection decreased by 33% from 1998 through 2001 4 and in the UK where the cost for managing ED in NHS the ICI occupied 26.6% in 1997 and became negligible in 2000. 5 A study in Italy demonstrated that men with ED who were switched from stable ICI therapy to sildenafil expressed greater overall treatment satisfaction, better ease of use, naturalness of Three treatment modalities for erectile dysfunction B-P Jiann et al erectile process, and intention to continue treatment with sildenafil.…”
Section: Discussionsupporting
confidence: 70%
“…A report showed the number of prescriptions of sildenafil increased 87% from 7.5 to 14 million from 1998 through 2001 in the USA. 4 The growing sales of sildenafil in Taiwan followed this trend too.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…22 In contrast, urologists constituted 91.1% of sildenafil prescribers at our institution in Taiwan. Since ED is associated with multiple factors, more than 40% of our subjects sustained various chronic diseases that required long-term medication and regular followup.…”
Section: Discussionmentioning
confidence: 99%
“…However, the introduction of sildenafil, a specific phoshodiesterase 5 inhibitor in 1998, as the first oral drug with proven efficacy and safety in the treatment of erectile dysfunction has changed dramatically the management of our patients [1]. Sildenafil prescriptions raised significantly while the use of intracavernosal injections and intraurethral alprostadil-that were the only approved pharmacotherapiesremained unchanged [2]. Later apomorphine-a central acting dopaminergic agonist-and last year, two new phosphodiesterase 5 inhibitors-tadalafil and vardenafil-expanded treatment options.…”
Section: Introductionmentioning
confidence: 99%